The plasticity of germ cell cancers and its dependence on the cellular microenvironment. Issue 8 (28th February 2017) - Nettersheim, Daniel; Schorle, Hubert
Abstract: So far, the understanding of germ cell cancer (GCC) pathogenesis is based on a model, where seminomas and non‐seminomas represent distinct entities although originating from a common precursor termed germ cell neoplasia in situ (GCNIS). Embryonal carcinomas (ECs), the stem cell population of the non‐seminomas, is pluri‐ to totipotent and able to differentiate into cells of all three germ layers, giving rise to teratomas or tumours mimicking extraembryonic tissues (yolk sac tumours, choriocarcinomas). With regard to gene expression, (epi)genetics and histology, seminomas are highly similar to GCNIS and primordial germ cells, but limited in development. It remains elusive, whether this block in differentiation is controlled by cell intrinsic mechanisms or by signals from the surrounding microenvironment. Here, we reviewed the recent literature emphasizing the plasticity of GCCs, especially of seminomas. We propose that this plasticity is controlled by the microenvironment, allowing seminomas to transit into an EC or mixed non‐seminoma and vice versa. We discuss several mechanisms and routes of reprogramming that might be responsible for this change in the cell fate. We finally integrate this plasticity into a new model of GCC pathogenesis, allowing for an alternative view on the dynamics of GCC development and progression.